A Replication of "Economic Development and the Impacts of Natural Disasters" (Economics Letters 2007). (March 2015) - Mercer, Robert; Reed, W. Robert
This study replicates the empirical findings of Toya and Skidmore (2007), henceforth TS, and performs a variety of robustness checks. Using an extensive data set of international disasters, TS report that a number of economic development variables are significantly related to mitigation of adverse disaster consequences. We are able to exactly replicate their findings. Our robustness checks consist of two parts. First, we update TS's original data set, with respect to both variable values and years of coverage. We then address a number of estimation and specification issues. With one exception, our robustness checks fail to find strong evidence that economic development variables (income, educational attainment, size of government, economic openness, and financial sector development) are statistically related to either fatalities or economic damages. The exception is that we find that higher national income is associated with reduced economic losses (as a share of gross domestic product) from natural disasters.